Answer:
64
Step-by-step explanation:
put branileist
Answer:
The polynomial is ;
x^3 -2x^2 -13x - 10
Step-by-step explanation:
Given the zeros, we set them to equal zero so as to get the linear factors
Mathematically, that will be as follows;
x = -2
x + 2
x = 5
x-5
x = -1
x + 1
So we have the polynomial as;
(x + 1)(x + 2)(x-5)
= (x -5)(x^2 + 3x + 2)
= x^3+ 3x^2 + 2x -5x^2 -15x - 10
= x^3 -2x^2 -13x - 10
Answer:
1.) Exact form: x = -13/6
Decimal Form: x = -2.6 ( repeated )
Mixed number form: x = -2 1/6
2.) x = -18
3.) Exact form: x = 5/3
Decimal Form: x = 1.6 ( repeated )
Mixed Number form: x = 1 2/3
Step-by-step explanation:
(2x^2+3x+4)(x^3+4x^2+3x)(x+4)
First use the distributive property for the first two:
(2x^5+8x^4+6x^3+3x^4+12x^3+9^2+4x^3+16x^2+12x)(x+4)
And then combine like terms:
(2x^5+11x^4+22x^3+25x^2+12x)(x+4)
Continue use the distributive property:
(2x^6+11x^5+22x^4+25x^3+12x^2+8x^5+44x^4+88x^3+100x^2+48x)
Continue combine like terms:
(2x^6+19x^5+66x^4+113x^3+112x^2+48x)
And that is your final answer.
Hope that help:)
3x+12=6 will give you x=2
And
-2=4-3x will give you x=-2